Knowledge and attitude regarding reproductive health and sex education among school teachers of Dhading, Nepal - Badan Tuladhar, Jyoti; Barakoti, Yojana; Sakha, Rashmi; Khanal, Anjana; Khanal, Pratibha (Journal of Chitwan Medical College, 2026)
Introduction: Reproductive health and sex education (RHSE) is essential for adolescent development. Teachers are key facilitators, yet their preparedness in Nepal is understudied. This study assessed the knowledge and attitude regarding RHSE among school teachers in Dhading, Nepal. Methods: A cross-sectional study was conducted from Feb to Apr 2023 among teachers from six secondary schools in Benighat Rorang Rural Municipality, Dhading, Nepal. Ethical approval was obtained. A census method was used. Data were collected via a pretested, structured, self-administered questionnaire. Knowledge and attitude scores were categorized using Bloom's and Bloom's cut-off points, respectively. Descriptive statistics, chi-square tests, and Spearman's correlation were used for analysis in IBM SPSS version 21, with a significance level of p≤0.05. Results: Among 104 teachers, the mean age was 34.98±10.37 years. More than half had an average level of knowledge (54.8%, n=57), and the majority showed a neutral attitude (64.4%, n=67). A significant association was found between sex and knowledge level (p=0.020), with a higher proportion of males having good knowledge. A weak positive correlation between knowledge and attitude was observed (r=0.015, p=0.82). Conclusions: The study indicates that selected teachers in Dhading possess average knowledge and a neutral attitude toward RHSE. Knowledge is associated with sex, and improved knowledge may foster a more positive attitude. Mandatory, culturally sensitive training programs are recommended to enhance teachers' capacity to deliver effective RHSE.